PD-1 inhibits T cell proliferation by upregulating p27 and p15 and suppressing Cdc25A - Patsoukis, Nikolaos (Landes Bioscience, 2012)
The programmed cell death-1 (PD)-1 receptor (CD279) is a potent T cell inhibitor with a critical role in peripheral tolerance, but it can also compromise anti-viral and antitumor T cell responses. The effects of PD-1 on the cell cycle leading to inhibition of T cell expansion are poorly understood. Recently, we examined the effects of PD-1 on the molecular control of the cell cycle machinery and on TCR-activated signaling pathways that regulate these downstream outcomes. Our studies showed that PD-1 blocks cell cycle progression in the G(1) phase. PD-1 did not alter the expression of G(1) phase cyclins or cyclin-dependent kinases (Cdks) but, instead, suppressed the transcription of SKP2, the substrate recognition component of the SCF(Skp2) ubiquitin ligase that leads p27(kip1) to degradation and resulted in accumulation of p27(kip1). Subsequently, T cells receiving PD-1 signals displayed impaired Cdk2 activation and failed to phosphorylate two critical Cdk2 substrates, the retinoblastoma gene product (Rb) and the TGFβ-specific transcription factor Smad3, leading to suppression of E2F target genes but enhanced Smad3 transactivation. These events resulted in upregulation of the Cdk4/6 inhibitor p15(INK4B) and repression of the Cdk-activating phosphatase Cdc25A. The suppressive effect of PD-1 on Skp2 expression was mediated by inhibition of both PI3K/Akt and Ras/MEK/Erk pathways and was only partially reversed by IL-2, which restored activation of MEK/Erk but not Akt. Thus, PD-1 targets Ras and PI3K/Akt signaling to inhibit transcription of Skp2 and to activate Smad3 as an integral component of a pathway that regulates blockade of cell cycle progression in T lymphocytes. Here, we discuss the detailed sequence of these signaling events and their implications in mediating cell-intrinsic and -extrinsic mechanisms that inhibit proliferation of T effector cells in response to PD-1-mediated signaling.